Oestrous Behavior of Cows Induced by Different Hormones - Jamili, Muhammad Arsan; Hardianto, Hardianto; Susanti, Handayani Indah; Mappanganro, Rasyidah (JAS, 2025)
Prostaglandin and estrogen hormones are two types of hormones commonly used in heat synchronization aimed at inducing earlier estrus in livestock. This study aims to determine the success rate of artificial insemination (AI) in beef cattle synchronized in heat with different hormones. The research method used is a Completely Randomized Design (CRD) consisting of 3 treatments and 4 replications: P0 (natural estrus), P1 (prostaglandin injection), and P2 (estrogen injection). The parameters tested in this study include the percentage of estrus, intensity of estrus and time of estrus symptoms. The analysis used is Analysis of Variance (ANOVA). The results indicate that the percentage of cattle showing signs of estrus in all three treatments reached 100%. The intensity of estrus in each treatment was assessed in three categories: clear estrus (score 3+++), moderate estrus (score 2++), and low estrus (score 1+). The results showed that in P0 and P2, 50% of the cattle exhibited clear estrus and 50% moderate estrus, while in P1, 66.7% showed clear estrus and 33.3% moderate estrus. The onset of estrus symptoms in P0 occurred on average at hour <480 or days 18-20 from the first to the second estrus cycle, whereas in P1 and P2, it appeared at hour 48 or day 2 after injection.